Performance and carcass traits of steers submitted to supplementation in the dry season - Domingues, Miguel Sales [UNESP]; Lupatini, Gelci Carlos [UNESP]; Andrighetto, Cristiana [UNESP]; de Araújo, Laura Costa Alves [UNESP]; Cardassi, Marianna Rosa [UNESP]; Polli, Daniel [UNESP]; Medeiros, Saulo Flaviano [UNESP]; da Fonseca, Ricardo [UNESP]; dos Santos, Juliana Aparecida Alves [UNESP] (FapUNIFESP (SciELO), 2014)
The objective of this study was evaluate the effect of two supplementation strategies in the dry season on performance and carcass traits of steers finished on marandu grass. The experimental design was completely randomized with two treatments and eighteen repetitions per treatment. The treatments consisted of ad libitum protein mineral salt (PMS) and supplementation with concentrate (SC) with 0.5% of body weight. It was used 36 Nelore steers with initial weight of 417kg and 20 months of age. After slaughter, carcasses were weighted, identified and cooled for 24 hours. Carcass yield, ribeye, fat thickness, pH and marbling score were measured. The animals supplemented with concentrate had higher (P<0.01) average daily weight gain (0.562kg) and higher fat thickness adjusted to 100kg carcass than animals supplemented with protein mineral salt (0.395kg), but did not differed (P>0.01) in relation to carcass weight, carcass yield, ribeye, pH and marbling. The results show that the supplementation with concentrate accelerates gains, allowing early and better condition of slaughter and the use of protein mineral salt with adequate forage mass may be an alternative supplementation because less need for structure, control consumption, lower labor and greater ease in supply.
Desempenho e características da carcaça de novilhos submetidos à suplementação na seca
Keywords: Deferring; Marandu; Ribeye area; Urochloa brizantha